Novel long-chain neurotoxins from Bungarus candidus distinguish the two binding sites in muscle-type nicotinic acetylcholine receptors - Utkin, YN; Kuch, U; Kasheverov, IE; Lebedev, DS; Cederlund, E; Molles, BE; Polyak, I; Ivanov, IA; Prokopev, NA; Ziganshin, RH; Jornvall, H; Alvelius, G; et al. (Portland Press, 2019)
αδ-Bungarotoxins, a novel group of long-chain α-neurotoxins, manifest different affinity to two agonist/competitive antagonist binding sites of muscle-type nicotinic acetylcholine receptors, being more active at the interface of α-δ-subunits. Three isoforms (αδ-BgTx-1-3) were identified in Malayan Krait ( Bungarus candidus ) from Thailand by genomic DNA analysis; two of them (αδ-BgTx-1 and 2) were isolated from its venom. The toxins comprise 73 amino acid residues and 5 disulfide bridges, being homologous to α-bungarotoxin (α-BgTx), a classical blocker of muscle-type and neuronal α7, α8, and α9α10 nicotinic acetylcholine receptors. The toxicity of αδ-BgTx-1 (LD50 0.17-0.28 μg/g mouse, i.p. injection) is essentially as high as that of α-BgTx. In the chick biventer cervicis nerve-muscle preparation, αδ-BgTx-1 completely abolished acetylcholine response, but in contrast to the block by α-BgTx, acetylcholine response was fully reversible by washing. αδ-BgTxs, similar to α-BgTx, bind with high affinity to α7 and muscle-type nicotinic acetylcholine receptors. However, the major difference of αδ-BgTxs from α-BgTx and other naturally-occurring α-neurotoxins is that αδ-BgTxs discriminate the two binding sites in the Torpedo californica and mouse muscle nicotinic acetylcholine receptors showing up to two orders of magnitude higher affinity for the α-δ site as compared to α-ε or α-γ binding site interfaces. Molecular modeling and analysis of the literature provided possible explanations for these differences in binding mode; one of the probable reasons being the lower content of positively charged residues in αδ-BgTxs. Thus, αδ-BgTxs are new tools for studies on nicotinic acetylcholine receptors.